The ‘Urban Elements’ method for teaching parametric urban design to professionals - Aurel von Richthofen; Katja Knecht; Yufan Miao; Reinhard König (Frontiers of Architectural Research, 2018)
The article proposes a method for teaching advanced urban design to working professionals in Singapore. The article aims to expand the discourse on parametric urban design education by introducing ‘Urban Elements’ as conceptual urban design instruments with an inherent rule-based logic, which can help to bridge gaps in teaching parametric urban design thinking. As case study we present a course developed for and delivered to the Urban Redevelopment Authority (URA) in Singapore in 2017 by the Future Cities Laboratory at the Singapore-ETH Centre. The article reports on the pedagogical method, course results and course feedback. The main difficulties of teaching professionals in parametric urban design are described and possible reasons and improvements are discussed. The results show that participants using the ‘Urban Elements’ method successfully linked theoretical input to urban design problems, applied evidence-based urban design strategies to these problems, and developed parametric definitions to explore the solution spaces of these urban design challenges. The teaching methodology presented opens up a new research field for urban design pedagogy at the intersection of explicating urban design intent, integrating multidisciplinary knowledge and exploring new software driven tools. Keywords: Urban design education, Parametric urban design, Singapore, Urban Elements